Penyuluhan Pemanfaatan Limbah Sekam Menjadi Arang Sekam Di Desa Kepur Kecamatan Muara Enim - Framita, Rabecha Maros; Aliyah, Aliyah; Fratiwi, Inike (Jumat Pertanian: Jurnal Pengabdian Masyarakat, 2024)
To date, the husk waste generated from post-harvest processing has been discarded without any subsequent processing for use or commercial value. In light of this phenomena, it is imperative to instruct the farmers of Kepur Village on the conversion of husk waste into husk charcoal, enabling its reutilization as an organic fertilizer integrated with planting medium. The service will be implemented in three phases: trials, counseling, and training.The trial results of the husk charcoal manufacturing equipment demonstrate that in one production process, 25 kg of dry husk raw material is required and generates an average of 19.67 kg, resulting in a total loss of 21.32%. If converted into rupiah, with an investment of IDR 25,000, dry husks will yield IDR 98,350 in one production phase.